Mesophyll conductance and reaction-diffusion models for CO2 transport in C3 leaves; needs, opportunities and challenges. (November 2016) - Berghuijs, Herman N.C.; Yin, Xinyou; Ho, Q. Tri; Driever, Steven M.; Retta, Moges A.; Nicolaï, Bart M.; Struik, Paul C.
Highlights: Mesophyll conductance models cannot fully explain the mechanism of CO2 transport in the mesophyll. Reaction-diffusion models can identify targets to increase mesophyll conductance. Abstract: One way to increase potential crop yield could be increasing mesophyll conductance g m . This variable determines the difference between the CO2 partial pressure in the intercellular air spaces ( C i ) and that near Rubisco ( C c ). Various methods can determine g m from gas exchange measurements, often combined with measurements of chlorophyll fluorescence or carbon isotope discrimination. g m lumps all biochemical and physical factors that cause the difference between C c and C i . g m appears to vary with C i . This variability indicates that g m does not satisfy the physical definition of a conductance according to Fick's first law and is thus an apparent parameter. Uncertainty about the mechanisms that determine g m can be limited to some extent by using analytical models that partition g m into separate conductances. Such models are still only capable of describing the CO2 diffusion pathway to a limited extent, as they make implicit assumptions about the position of mitochondria in the cells, which affect the re-assimilation of (photo)respired CO2 . Alternatively, reaction-diffusion models may be used. Rather than quantifying g m, these models explicitly account for factors that affect the efficiency of CO2 transport in the mesophyll. These models provide a better mechanistic description of the CO2 diffusion pathways than mesophyll conductance models. Therefore, we argue that reaction-diffusion models should be used as an alternative to mesophyll conductance models, in case the aim of such a study is to identify traits that can be improved to increase g m .